Characterization of cardiac involvement in patients with LMNA splice-site mutation–related dilated cardiomyopathy and sudden cardiac death - Ling, Xuebin; Hou, Yanjun; Jia, Xingyu; Lan, Youling; Wu, Xiaoping; Wu, Julan; Jie, Wei; Liu, Hui; Huang, Shan; Wan, Zhenling; Li, Tianfa; Guo, Junli; et al. (Frontiers in Genetics, 2024)
LMNA splicing mutations occur in 9.1% of cases with cardiac involvement, but the phenotype and severity of disease they cause have not yet been systematically studied. The aim of this study was to understand the clinical and pathogenic characteristics of the LMNA splice-site mutation phenotype in patients with LMNA -related dilated cardiomyopathy (DCM) and sudden cardiac death (SCD). First, we reported a novel family with LMNA-related DCM and SCD, and the clinical characteristics of all current patients with LMNA splicing mutations were further summarized through the ClinVar database. Seventeen families with a total of 134 individuals, containing a total of 15 LMNA splicing mutation sites, were enrolled. A total of 42 subjects (31.3%) had SCD. Compared with the non-DCM group (n=56), the patients in the DCM group (n=78) presented a lower incidence of atrioventricular block (AVB) (p=0.015) and higher incidence rates of non-sustained ventricular tachycardia (p=0.004) and implantable cardioverter defibrillator (ICD) implantation (p=0.005). Kaplan-Meier survival analysis showed that the patients with pacemaker (PM) implantation had a significantly reduced occurrence of SCD compared with those without PM implantation (log-rank p<0.001), while there was no significant difference in ICD implantation between the two groups (log-rank p=0.73). Second, we identified an LMNA c.513+1 G>A mutation in the reported family, and pathogenic prediction analysis showed that the mutation site was extremely harmful. Next, we conducted gene expression and cardiac pathological biopsy studies on the proband of this family. We found that the expression of normal LMNA mRNA from the proband was significantly downregulated in peripheral blood mononuclear cells compared with healthy individuals. Finally, we comprehensively summarized the pathological characteristics of LMNA-related DCM, including hypertrophy, atrophy, fibrosis, white blood cell infiltration, intercalated disc remodeling, and downregulation of desmin and connexin 43 (Cx43) expression. Above all, cardiac involvement in patients with LMNA splice-site mutation presented with a high rate of SCD. Implanting a pacemaker significantly reduced the SCD rate in non-DCM patients with AVB. The pathogenic characterization not only involved suppressed expression of the healthy LMNA allele, but was also associated with abnormal expression and distribution of desmin and Cx43.